The Role of Eosinophils in Bullous Pemphigoid: A Developing Model of Eosinophil Pathogenicity in Mucocutaneous Disease - Amber, Kyle T.; Valdebran, Manuel; Kridin, Khalaf; Grando, Sergei A. (Frontiers in Medicine, 2018)
Bullous pemphigoid (BP) is an autoimmune blistering disease which carries a significant mortality and morbidity. While historically BP has been characterized as an IgG driven disease mediated by anti-BP180 and BP230 IgG autoantibodies, developments in recent years have further elucidated the role of eosinophils and IgE autoantibodies. In fact, eosinophil infiltration and eosinophilic spongiosis are prominent features in BP. Several observations support a pathogenic role of eosinophils in BP: IL-5, eotaxin, and eosinophil-colony stimulating factor are present in blister fluid; eosinophils line the dermo-epidermal junction (DEJ) in the presence of BP serum, metalloprotease-9 is released by eosinophils at the site of blisters; eosinophil degranulation proteins are found on the affected basement membrane zone as well as in serum corresponding with clinical disease; eosinophil extracellular DNA traps directed against the basement membrane zone are present, IL-5 activated eosinophils cause separation of the DEJ in the presence of BP serum; and eosinophils are the necessary cell required to drive anti-BP180 IgE mediated skin blistering. Still, it is likely that eosinophils contribute to the pathogenesis of BP in numerous other ways that have yet to be explored based on the known biology of eosinophils. We herein will review the role of eosinophils in BP and provide a framework for understanding eosinophil pathogenic mechanisms in mucocutaneous disease.